2019
DOI: 10.4236/jmf.2019.93024
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Impact of Information Security Breaches on Stock Market Returns and VaR Backtest

Abstract: This paper wants to analyse the cyber-risk impact on economy in particular on the returns of the companies suffering information braches. The problem has become very interesting in recent years in the literature for the large dependence of the business with cyber world. The analysis focuses on event study in which the impact of cyber-attacks on stock prices of selected companies is investigated. Cyber-risk phenomenon is processed considering a portfolio of targeted assets, in order to analyse their correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The research conducted showed that the market provided a negative return on investment in the period after data breach as a result of cyber attacks (Kammoun, 2019). Another direction of research includes the impact of cyber risk on return on shares of enterprises that suffer from some information gaps (Colivicchi, Vignaroli, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research conducted showed that the market provided a negative return on investment in the period after data breach as a result of cyber attacks (Kammoun, 2019). Another direction of research includes the impact of cyber risk on return on shares of enterprises that suffer from some information gaps (Colivicchi, Vignaroli, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%